Drinking patterns, alcoholic beverage types, and esophageal cancer risk in Africa: a comprehensive systematic review and meta-analysis - Ndebia, Eugene Jamot; Kamsu, Gabriel Tchuente (Frontiers in Oncology, 2023)
Africa is the continent most affected by esophageal cancer in the world. Alcoholic beverages are controversially blamed, as esophageal cancer is a rare disease in several other countries ranked in the top 10 for consumption of alcoholic beverages. This study aims to conduct a comprehensive systematic review of published literature, statistically summarizing the strength of the association between drinking patterns and types, and the risk of esophageal cancer in Africa. A computerized search of reputable databases such as Medline/PubMed, EMBASE, Web of Science, and African Journals Online was performed to identify relevant studies published up to September 2023. The quality of the studies was evaluated using the Newcastle-Ottawa scale for case-control studies and the Agency for Healthcare Research and Quality tool for cross-sectional studies. A funnel plot and Egger test were utilized to assess potential publication bias. Meta-analyses were conducted using random-effects models with RevMan 5.3 and Stata software to estimate summary effects. The systematic review identified a total of 758,203 studies, primarily from Eastern and Southern Africa. The pooled samples across all studies comprised 29,026 individuals, including 11,237 individuals with cancer and 17,789 individuals without cancer. Meta-analysis revealed a significant association between alcohol consumption and the risk of esophageal cancer (odds ratio [OR] = 1.81; 95% confidence interval [CI],). Further analysis based on the frequency of alcoholic beverage consumption indicated a stronger association with daily (OR = 2.38; 95% CI, 1.81-3.13) and weekly (OR = 1.94; 95% CI, 1.32-2.84) drinkers in contrast to occasional drinkers (OR = 1.02; 95% CI, 0.81-1.29). Additionally, consumption of traditional alcoholic beverages was significantly associated with the risk of esophageal cancer in African populations (OR = 2.00; 95% CI, 1.42-2.82). However, no relationship has been established between the exclusive consumption of non-traditional drinks and the risk of esophageal cancer. In conclusion, the results of this study confirm the hypothesis that daily and weekly drinking patterns, significantly increase the risk of esophageal cancer in Africa, while occasional consumption does not show a significant association. Additionally, the consumption of traditional alcoholic beverages is notably linked to the risk of esophageal cancer in African populations.